A prospective observational study of the main features of nocturnal leg cramps in primary care (Swiss Medical Weekly, 2019)
OBJECTIVE There are few data available regarding the characteristics of nocturnal leg cramps in primary care. However, this condition is particularly common among older adults and often causes sleep disturbances, which can seriously affect quality of life. We aimed to investigate the main characteristics of nocturnal leg cramps occurring over a two-week period in patients visiting primary care physicians. METHODS This prospective observational study was conducted in western Switzerland from January 2015 until June 2016. Twenty primary care physicians were asked to recruit up to 20 consecutive patients over the age of 50 who had suffered from cramps in the previous three months. Patients completed a daily log during a two-week period, reporting the number and duration (in minutes) of their cramps. They also reported the severity of the cramps and their level of cramp-related sleep disturbance on a scale from 0 to 10. Crude and adjusted associations between the number of cramps and patient characteristics were computed using a generalised mixed effects model (Poisson). RESULTS Of 550 consecutive patients, 233 agreed to be contacted for participation. Of these, 129 signed the consent to participation form and all completed the questionnaire and the daily log (men: 67%; mean age: 71 years; follow-up rate: 100%). Overall, 41% of patients were suffering from hypertension, 20% from dyslipidaemia, 19% from sleep disturbances and depression, and 6% from diabetes. Half the patients reported having already used a treatment against nocturnal leg cramps in the past, and 25% were currently using magnesium. Most of them also used medication for other health problems (mean number 3.7 per patient; psychotropic drugs: 36%). Patients had a median of two cramps per week, which were generally mild (median rating of 0.7 on a 10-point scale) and short (median: 0.4 min), leading to mild sleep disturbances (median rating of 0.8 on a 10-point scale). Multivariate analysis showed that older age and previous cramp treatment were associated with more cramps per day, while the use of magnesium and/or psychotropic drugs was associated with fewer cramps per day. CONCLUSIONS Although nocturnal leg cramps are common among older patients in primary care, the disease burden of nocturnal leg cramps only appears to be severe in a minority of patients.